2019
DOI: 10.1108/ijrdm-09-2017-0184
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable clothing: perspectives from US and Chinese young Millennials

Abstract: Purpose The purpose of this paper is to understand US and Chinese young Millennials’ perceptions of and consumption behaviour towards sustainable apparel products. Design/methodology/approach Quantitative research was conducted, and empirical data were collected from 590 US college students and 379 Chinese college students. Findings For both US and Chinese young Millennials, this study provides consistent empirical results of the positive and significant effects of young Millennials’ apparel sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 81 publications
3
90
1
2
Order By: Relevance
“…Thus, the last users have a key role to play in sustainability in the fashion field. Early research on sustainable fashion showed that a few consumers were interested in sustainable fashion [55][56][57][58], but more recent research shows that young consumers have a high interest in sustainable fashion [4,59]. Therefore, identifying the concept, consumer values, motivations, and behaviors associated with sustainable fashion is meaningful by analyzing current consumers' thoughts based on the words they use in the social media.…”
Section: Sustainable Fashion Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the last users have a key role to play in sustainability in the fashion field. Early research on sustainable fashion showed that a few consumers were interested in sustainable fashion [55][56][57][58], but more recent research shows that young consumers have a high interest in sustainable fashion [4,59]. Therefore, identifying the concept, consumer values, motivations, and behaviors associated with sustainable fashion is meaningful by analyzing current consumers' thoughts based on the words they use in the social media.…”
Section: Sustainable Fashion Consumptionmentioning
confidence: 99%
“…Thus, an individual consumption lifestyle is important for an ongoing sustainable development. Fortunately, young consumers, particularly Millennials and the Generation Z, have strong behavioral intentions to engage in sustainable consumption [3,4]. Considering the leading power of the young generation in the market, it is clear that the unsustainable consumption patterns will soon face change.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers need to have a base knowledge of these issues in order to make prepared and informed purchase decisions. With this knowledge, they can change their attitudes regarding sustainable apparel and, therefore, their purchase behaviour (Su et al, 2019). Younger generations specifically are becoming more aware of environmental issues along with the impact that apparel consumption has due to their connection and usage of the Internet and various social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They represent the largest generational cohort [2,23], so their purchasing power makes them an appealing target group for many consumer industries and attracts many companies towards understanding the needs and behavior of this customer base. Consequently, millennials have become a remarkable group for study given their distinctive behavior as compared to other generations [7], their sharing of common values [24,25], enjoyment of life experiences [26], pursuance of specific motivations [3,5,14,27], and purchasing behavior [24,28]. Millennials are characterized as having a higher education level than other generations [1,29] or by the intensive use and adaptation of technology in their daily lives [17,28,30,31].…”
Section: Food Naturalness and Millennials' Behaviormentioning
confidence: 99%